THE EFFECT OF FEEDING A COMBINATION OF MAGGOT (Hermetia illucens) AND TOUGH DRUGS ON THE INTESTINE HISTOLOGY OF SKINS (Channa striata) - Muhammadar A. A; Nurul Hasanah; Suraiya Nazlia; Dedi Ferdiansyah Putra; Asmawati M. Sail (Jurnal Penelitian Progresif, 2023)
Snakehead fish are carnivorous organisms that inhabit shallow waters such as muddy areas, calm currents, and rocky water areas for hiding places. This study aims to determine the effect of using a combination of maggot and fermented tofu dregs in feed on intestinal histology and snakehead fish survival. This research was conducted at the Fish Breeding and Rearing Laboratory, Faculty of Marine Affairs and Fisheries, Syiah Kuala University in February 2023 - March 2023 using a Completely Randomized Design method with 4 treatments and 4 replications. The parameter observed in this study was the intestinal surface area of ​​snakehead fish (Channa striata) using the formula of Sakamoto et al., (2000). The results of this study showed that the best treatment for the surface area of ​​snakehead fish intestinal villi was (64544.19 mm2) in treatment D with a combination of 60% fermented maggot flour + 10% fermented tofu dregs.